The plow, the pen and the sword - Keunzel, R. E. (Rudi E.), author.
1 online resource (xiii, 226 pages)
Keywords: "This book compares the cultures of the different social groups living in the Low Countries in the early Middle Ages. Clergy, nobility, peasants and townsmen greatly varied in their attitudes to labor, property, violence, and the handling and showing of emotions. Keunzel explores how these social groups looked at themselves as a group, and how they looked at the other groups. Image and self-image could differ radically. The results of this research are specified and tested in four case studies on the interaction between group cultures, focusing respectively on the influence of oral and written traditions on a literary work, rituals as a means of conflict management in weakly centralized societies, stories as an expression of an urban group mentality, and beliefs on death and the afterlife"--Provided by publisher.